Morphological and autoradiographic studies on the corneal and limbal epithelium of rabbits - Goes, Rejane Maira [UNESP] (2008)
The investigation was centered on the morphological features of the conjunctiva-cornea transition (limbus) of the rabbit eye and the proliferative behavior of its epithelium. The eyes were processed for examination with light and electron microscopy, as well as for autoradiography after intravitreal injection of [H-3]thymidine ([H-3]TdR). At the sites of extraocular muscle insertion, the vascularization of the stroma extended to the peripheral cornea, and the limbal epithelium was thin with its basal stratum made up by clear cuboidal cells. In between the muscle insertions, the cuboidal clear cells, as well as the stroma blood vessels; were scarce. At the light microscope level, the basement membrane was distinct in the cornea but not in the limbus or the conjunctiva. Autoradiographs demonstrated that, at the limbus, the basal cells migrated very quickly to the suprabasal region and remained there up to the 28-day interval. Labeled cells were identified in all epithelial layers of the cornea, including the basal one, at 21 and 28 days but not in the limbal basal clear cells. The rate of renewal of conjunctival epithelium was similar to that observed for the transition with scarce clear cells. The high-resolution autoradiographs demonstrated that the basal cuboidal clear limbal cells exhibit a quick renewal and that they are not label-retaining cells. These latter ones were detected all over the corneal epithelium and in the suprabasal layers of the limbus up to 28 days, in physiological conditions, without the need of stimulation by damage to the corneal epithelium.